LEVERAGE, LIKUIDITAS, DAN PROFITABILITAS DALAM MEMPREDIKSI FINANCIAL DISTRESS: PERAN MODERASI DEWAN PENGAWAS SYARIAH - Amardi, Angelika Putri; Zulfikar, Zulfikar (Unitri Press, 2025)
Purpose: This research attempts to investigate the impact of leverage, liquidity, and profitability on financial distress with the sharia supervisory board as a moderating variable, Methods: This kind of study makes use of a quantitative method, Analysis data: Data were analyzed using multiple linear regression and moderated regression analysis, Result and discussions: The outcomes of this investigation demonstrate that leverage has a negative and significant effect on financial distress, while liquidity has a positive and significant effect. Conversely, profitability has no effect on financial distress. Furthermore, the sharia supervisory board is unable to moderate the relationship between leverage, liquidity, or profitability on financial distress, Conclusion: This can be considered as financial risk management in the Islamic banking sector, as well as revealing the limitations of the role of the sharia supervisory board in mitigating financial distress.